Characterizing the reduction of stimulation artifact noise in a tripolar nerve cuff electrode by application of a conductive shield layer. (February 2017) - Sabetian, Parisa; Sadeghlo, Bita; Zhang, Chengran Harvey; Yoo, Paul B
Highlights: A method is proposed for significantly improving peripheral nerve recording. The method relies on a conductive shield layer (CSL) to divert artifact current. Computer simulations show an 85% decrease in the recorded artifact signal. In vivo study confirms the effects of the CSL for a tripolar nerve cuff electrode. Abstract: Tripolar nerve cuff electrodes have been widely used for measuring peripheral nerve activity. However, despite the high signal-to-noise ratio levels that can be achieved with this recording configuration, the clinical use of cuff electrodes in closed-loop controlled neuroprostheses remains limited. This is largely attributed to artifact noise signals that contaminate the recorded neural activity. In this study, we investigated the use of a conductive shield layer (CSL) as a means of reducing the artifact noise recorded by nerve cuff electrodes. Using both computational simulations and in vivo experiments, we found that the CSL can result in up to an 85% decrease in the recorded artifact signal. Both the electrical conductivity and the surface area of the CSL were identified as important design criteria. Although this study shows that the CSL can significantly reduce artifact noise in tripolar nerve cuff electrodes, long-term implant studies are needed to validate our findings.